Reduction of a Tetrafluoroterephthalonitrile‐β‐Cyclodextrin Polymer to Remove Anionic Micropollutants and Perfluorinated Alkyl Substances from Water. (24th July 2019) - Klemes, Max J.; Ling, Yuhan; Ching, Casey; Wu, Congyue; Xiao, Leilei; Helbling, Damian E.; Dichtel, William R.
Abstract: Organic micropollutants (MPs) are anthropogenic substances that contaminate water resources at trace concentrations. Many MPs, including per‐ and polyfluorinated alkyl substances (PFASs), have come under increased scrutiny because of their environmental persistence and association with various health problems. A β‐cyclodextrin polymer linked with tetrafluoroterephthalonitrile (TFN‐CDP) has high affinity for cationic and many neutral MPs from contaminated water because of anionic groups incorporated during the polymerization. But TFN‐CDP does not bind many anionic MPs strongly, including anionic PFASs. To address this shortcoming, we reduced the nitrile groups in TFN‐CDP to primary amines, which reverses its affinity towards charged MPs. TFN‐CDP exhibits adsorption distribution coefficients (log  K D values) of 2–3 for cationic MPs and −0.5–1.5 for anionic MPs, whereas the reduced TFN‐CDP exhibits log  K D values of −0.5–1.5 for cationic MPs and 2–4 for anionic MPs, with especially high affinity towards anionic PFASs. Kinetic studies of the removal of 10 anionic PFASs at environmentally relevant concentrations showed 80–98 % removal of all contaminants after 30 min and was superior to commercial granular activated carbon. These findings demonstrate the scope and tunability of CD‐based adsorbents derived from a single polymerization and the promise of novel adsorbents constructed from molecular receptors. Abstract : Organische Mikroverunreinigungen (MPs), einschließlich per‐ und polyfluorierter Alkylsubstanzen (PFASs), sind Spurenverunreinigungen im Wasser. Ein mit Tetrafluorterephthalonitril (TFN‐CDP) verknüpftes β‐Cyclodextrinpolymer hat eine hohe Affinität zu kationischen und neutralen MPs, bindet anionische PFASs aber nur schwach. Durch Reduktion der Nitrilgruppen in TFN‐CDP zu primären Aminen wird ein Material erhalten, das anionische PFASs entfernt.